Introducing morphology - Lieber, Rochelle (Cambridge Cambridge university press, 2016)
This book provides data from a wide variety of languages, it includes hands-on activities such as 'challenge' boxes, designed to encourage students to gather their own data and analyze it, work with data on websites, perform simple experiments, and discuss topics with each other. There is also an extensive introduction to the terms and concepts necessary for analyzing words.
Includes index
Keywords: Cơ bản